What determines human body odour?. Issue 5 (May 2014) - Hamada, Kaoru; Haruyama, Sanehito; Yamaguchi, Takashi; Yamamoto, Kayo; Hiromasa, Kana; Yoshioka, Manabu; Nishio, Daisuke; Nakamura, Motonobu
Abstract Human body odour and earwax type are genetically dependent on a single‐nucleotide polymorphism (SNP) located in the ABCC11 gene. So far, it still remains to be clear how SNP in the ABCC11 gene is associated with human malodour. In a recent issue of Experimental Dermatology, Baumann et al. propose one of the underlying molecular pathways. Although one of the amino acid conjugated of the odorants, Cys‐Gly‐3‐methyl‐3‐sulfanylhexanol (3M3SH), was not taken up by the transporter ABCC11, glutathione conjugate of 3MSH (SG‐3MSH) was transported by ABCC11. Moreover, SG‐3MSH was processed to 3M3SH by γ‐glutamyl‐transferase 1 (GGT1), which was abundantly expressed in apocrine sweat glands. These findings may pave a way for the pharmacogenetics of human body odour and the development of innovative deodorant products.